Free radical scavenging and tyrosinase inhibition activity of oils and sericin extracted from Thai native silkworms (Bombyx mori) - Manosroi A. (2014)
Oils and sericin were extracted from pupae and silk cocoons, respectively, of the five Thai native silkworms (Bombyx mori, Linnaeus (Bombycidae)), namely, Keawsakol, Nangnoi, Somrong, Nangleung, and Noneruesee, which are variations of the same species. The oils were extracted by a hot process using Soxhlet apparatus and a cold process using petroleum ether, while sericin was extracted by basic hydrolysis and autoclaving. Sericin from the five Thai native silkworms showed free radical scavenging activity lower than the standard antioxidants (vitamin C, vitamin E, and BHT) by about 20100-fold, but all oils gave higher activity than that of the standard linoleic acid by 1122-fold. Oil extracted from Noneruesee by the cold process gave the highest DPPH scavenging activity, compared with other oil samples. All sericin samples showed tyrosinase inhibition activity with IC50 values in the range of 1.218.76mg/mL, but only oils from Noneruesee extracted by the hot process, and Nangleung, Somrong, and Noneruesee extracted by the cold process, showed this activity. Oil extracted by the hot process and sericin by basic hydrolysis from Noneruesee gave the highest tyrosinase inhibition activity, but lower than that of the standards vitamin C and kojic acid by 2049 and 38 times, respectively. This study has suggested that sericin and oil from Noneruesee extracted by basic hydrolysis and the cold process, which gave the highest tyrosinase inhibition and free radical scavenging activity, respectively, can be applied in antiaging and whitening cosmetic products. © 2010 Informa UK Ltd.